Tolerância ao risco: uma análise sob a ótica comportamental - Cavalheiro, Everton Anger (2010)
The traditional view of financial theory proposes an implicit rationality in decision making. But the decisions taken by individuals have been inconsistent with such assumptions. In this context, the study of risk tolerance has become increasingly more significant in today's society, because the understanding of risk tolerance forms of investment decisions and in providing products that can meet these needs. Despite the significance of the research topic has been inconsistent, particularly with respect to its determinants. Historically, research has revolved around heuristics demographic and socioeconomic assumptions neglecting emotional, cognitive and behavioral related to financial decision-making. This study aims to evaluate what are the determinants of risk tolerance. For this, we conducted a survey to survey with 815 individuals living in Santa Maria, Rio Grande do Sul Data were collected through questionnaire and analyzed via factor analysis, statistical tests (ANOVA, t test and correlation) and analysis of regression. The results show three factors that explain the risk tolerance, which are: Emotion factor, factor effect Staying Out of Factor and Self-attribution. Regression were added six variables analized in Behavioral Finance, which are: banking money effect, cognitive dissonance, self-protection, over-confidence, perception of risk and opportunity, effect cost already incurred and two other variables associated with the materialism that are spending with expensive things and join before you spend. It was explained 34.92% of the total variance of the data through these exogenous variables. Overall, and consistent, the assumptions of unlimited rationality have been refuted, but consistent with prospect theory, which agrees with the numerous studies that demonstrate the violation of assumptions of rationality unlimited. The heuristics traditionally used for determining the level of risk tolerance, which implies a strong correlation between the demographic and socioeconomic characteristics were not significant in this study. The cognitive, emotional and behavioral decision making were more significant than this traditional vision of risk.